In Vitro Impact of Fluconazole on Oral Microbial Communities, Bacterial Growth, and Biofilm Formation - Louise Morais Dornelas-Figueira; Antônio Pedro Ricomini Filho; Roger Junges; Heidi Aarø Åmdal; Altair Antoninha Del Bel Cury; Fernanda Cristina Petersen (MDPI AG, 2023)
Antifungal agents are widely used to specifically eliminate infections by fungal pathogens. However, the specificity of antifungal agents has been challenged by a few studies demonstrating antibacterial inhibitory effects against Mycobacteria and Streptomyces species. Here, we evaluated for the first time the potential effect of fluconazole, the most clinically used antifungal agent, on a human oral microbiota biofilm model. The results showed that biofilm viability on blood and mitis salivarius agar media was increased over time in the presence of fluconazole at clinically relevant concentrations, despite a reduction in biomass. Targeted PCR revealed a higher abundance of Veillonella atypica, Veillonella dispar, and Lactobacillus spp. in the fluconazole-treated samples compared to the control, while Fusobacterium nucleatum was reduced and Streptococcus spp were not significantly affected. Further, we tested the potential impact of fluconazole using single-species models. Our results, using Streptococcus mutans and Streptococcus mitis luciferase reporters, showed that S. mutans planktonic growth was not significantly affected by fluconazole, whereas for S. mitis, planktonic growth, but not biofilm viability, was inhibited at the highest concentration. Fluconazole's effects on S. mitis biofilm biomass were concentration and time dependent. Exposure for 48 h to the highest concentration of fluconazole was associated with S. mitis biofilms with the most increased biomass. Potential growth inhibitory effects were further tested using four non-streptococcal species. Among these, the planktonic growth of both Escherichia coli and Granulicatella adiacens was inhibited by fluconazole. The data indicate bacterial responses to fluconazole that extend to a broader range of bacterial species than previously anticipated from the literature, with the potential to disturb biofilm communities.